PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA KEDAI ALOHA DI KOTA AMBON - Feky Reken; Nadya Nurlailya Ningsih; Ervan Togatorop (Jurnal Riset Bisnis, 2025)
This study empirically aims to examine the influence of customer satisfaction and price on purchasing decisions at Aloha Café in Ambon City. A quantitative approach was employed, with the research population consisting of consumers who had previously made purchases at Aloha Café. Data collection was carried out by distributing questionnaires using a purposive sampling technique, resulting in a total of 110 respondents. The collected data were analyzed through multiple linear regression, classical assumption tests, hypothesis testing, and the coefficient of determination (R²), with the assistance of SPSS version 26 software. The findings indicate that, partially, both customer satisfaction and price exert a positive and significant effect on purchasing decisions at Aloha Café in Ambon City